The origin and characterization of two new Mussaenda hybrids - Rosario, T. L. (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 2006)
Hybrids of mussaendas are being developed continuously by the College of Agriculture, University of the Philippines Los Banos. Two new hybrids namely, M. 'Gloria Macapagal-Arroyo' and M. 'Zenaida Umali' are hereby being named and characterized. M. 'Gloria Macapagal-Arroyo' is a cross between M. 'Doña Evangelina' (with red bracts) and M. 'Doña Aurora' (with white bracts). The bracts are 4.0 × 1.7 - 4.0 × 2.1 cm, oblong to ovate elliptic, basically white suffused with tiny rose areas and with claret rose margin. The flowers are orpiment orange, 1.5-1.8 cm across and sterile. It was named after the incumbent President of the Philippines and daughter of former President Diosdado Macapagal and former First Lady Evangelina Macapagal. M. 'Zenaida Umali' is one of the progenies generated from the embryo rescue of (M. philippica × M. 'Doña Aurora') × M. 'Paraluman'. The bracts of the female parent are creamy white while those of the male parent are claret rose with paler veins. M. 'Zenaida Umali' has creamy white bracts which are 6.5 × 4.0 - 8.0 × 4.5 cm in size, obovate, with veins slightly sunken giving the bracts a puckered, slightly cupping downward appearance. The flowers are sulfur yellow, 2.2 - 2.4 cm across and semi-fertile. This hybrid was named after the wife of Dr. Dioscoro L. Umali, former Dean of the College of Agriculture and who initiated the development of the mussaenda hybrids in the 1940s with the assistance of Mrs. Umali.